TATA KELOLA PENGEMBANGAN DESTINASI PARIWISATA KABUPATEN MAMUJU - Ratna Ratna; Edi Jusriadi; Dg Maklassa (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This study aims to identify and analyze the tourism area management policies carried out by the Department of Tourism and Culture of Mamuju Regency towards the development of an integrated tourist area. Reviewing and analyzing the contribution of the government, universities, private sector, community, and media in the development of tourism areas in Mamuju Regency. Efforts to develop human resources in the management of tourism objects at the tourism and culture department of Mamuju Regency. This research was conducted at the Department of Tourism and Culture of Mamuju Regency using qualitative methods with data collection techniques through observation and interviews with representatives of the Tourism Office, tourist destination managers, and tourists. The results of this study indicate that: 1) The governance policy for the development of tourism destinations is contained in the Regional Regulation of Mamuju Regency Number 5 of 2016 concerning the Regional Medium-Term Development Plan (RPJMD) of Mamuju Regency 2016-2021 which is contained in the 5th mission. 2) The implementation of governance policies for the development of tourist destinations in Mamuju Regency is carried out through the involvement and cooperation between the government and the private sector, universities, communities, and the media. 3) Based on the evaluation of the program, it was found that the factors that influence tourism development in Mamuju Regency are the supporting factors are the strategic location of the area and tourism supporting facilities while the inhibiting factors are policy problems, lack of budget, promotion of tourist destinations that have not been maximized, management of tourist destinations that are not optimal. not optimal, quality human resources to manage tourist destinations are still limited (not in accordance with the educational background of tourism) so that the impact on the governance system is not optimal. Keywords: Governance, Tourism, Triple Helix.